ANALISIS COST-BENEFIT DALAM PENENTUAN PRIORITAS PROGRAM SEKOLAH BERBASIS RAPOR PENDIDIKAN PADA PENYUSUNAN RKAS - Ulfana Hidayati; Dwi Cahyaningdyah (STKIP Subang, 2026)
The implementation of Data-Based Planning through Indonesia’s Education Report Card (Rapor Pendidikan) has encouraged schools to use educational quality data as the basis for planning and budgeting. However, various studies indicate that many schools still face difficulties in determining funding priorities that effectively address educational quality problems identified through the Education Report Card. This study aims to analyze the role of Cost-Benefit Analysis (CBA) in determining school program priorities based on the Education Report Card in the preparation of School Activity and Budget Plans (RKAS). This research employed a qualitative approach using a literature review method by examining educational policy documents, books, and scientific publications related to educational financing, data-based planning, Cost-Benefit Analysis, and educational decision-making. Data were analyzed through content analysis and thematic synthesis. The findings indicate that the Education Report Card serves as an important instrument for identifying school quality problems and priority improvement areas, while Cost-Benefit Analysis provides a systematic framework for comparing alternative programs based on their costs and expected benefits. The analysis demonstrates that integrating educational quality data with Cost-Benefit Analysis can support more objective, efficient, accountable, and outcome-oriented budgeting decisions. This study contributes to the discourse on educational financing by offering a conceptual perspective on the use of Cost-Benefit Analysis in strengthening evidence-based school budgeting practices through the utilization of Education Report Card data.